Utilization of Pharmaceutical Technology Methods for the Development of Innovative Porous Metasilicate Pellets with a Very High Specific Surface Area for Chemical Warfare Agents Detection - Jiří Zeman; Sylvie Pavloková; David Vetchý; Adam Staňo; Zdeněk Moravec; Lukáš Matějovský; Vladimír Pitschmann (MDPI AG, 2021)
Pharmaceutical technology offers various dosage forms that can be applied interdisciplinary. One of them are spherical pellets which could be utilized as a carrier in emerging second-generation detection tubes. This detection system requires carriers with high specific surface area (SSA), which should allow better adsorption of toxic substances and detection reagents. In this study, a magnesium aluminometasilicate with high SSA was utilized along with various concentrations of volatile substances (menthol, camphor and ammonium bicarbonate) to increase further the carrier SSA after their sublimation. The samples were evaluated in terms of physicochemical parameters, their morphology was assessed by scanning electron microscopy, and the Brunauer-Emmett-Teller (BET) method was utilized to measure SSA. The samples were then impregnated with a detection reagent o-phenylenediamine-pyronine and tested with diphosgene. Only samples prepared using menthol or camphor were found to show red fluorescence under the UV light in addition to the eye-visible red-violet color. This allowed the detection of diphosgene/phosgene at a concentration of only 0.1 mg/m3 in the air for samples M20.0 and C20.0 with their SSA higher than 115 m2/g, thus exceeding the sensitivity of the first-generation DT-12 detection tube.